2012
DOI: 10.1039/c2cc31147j
|View full text |Cite
|
Sign up to set email alerts
|

A heme degradation enzyme, HutZ, from Vibrio cholerae

Abstract: HutZ, one of the crucial proteins of the iron uptake system in Vibrio cholerae, was purified, which binds to heme at a stoichiometry of 1 : 1. In the presence of ascorbic acid, the HutZ-bound heme degrades via the same intermediates observed in heme oxygenase, suggesting that HutZ works as a heme degradation enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
137
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(152 citation statements)
references
References 24 publications
15
137
0
Order By: Relevance
“…HoloHupZ in SPB containing CPR, NADPH regeneration system, and catalase (as described above) was allowed to react for 5 h. The reaction mixture was then acidified with 10 mM HCl, and partitioned into pyridine (33 %) as described by (Uchida et al 2012). …”
Section: Acidification and Pyridine Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…HoloHupZ in SPB containing CPR, NADPH regeneration system, and catalase (as described above) was allowed to react for 5 h. The reaction mixture was then acidified with 10 mM HCl, and partitioned into pyridine (33 %) as described by (Uchida et al 2012). …”
Section: Acidification and Pyridine Extractionmentioning
confidence: 99%
“…A new family of bacterial proteins that degrade heme in vitro and have no homology to previously described enzymes was recently uncovered in Campylobacter jejuni (ChuZ) (Zhang et al 2011), Helicobacter pylori (HugZ) (Guo et al 2008;Hu et al 2011) and Vibrio cholerae (HutZ) (Liu et al 2012b;Uchida et al 2012). Proteins from this family form homodimers with a split b-barrel fold that is characteristic of FMN-binding proteins, but no FMN binding was demonstrated.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A candidate for a heme oxygenase-like enzyme to degrade heme is the cytoplasmic protein HutZ, which is needed for the efficient use of heme as an iron source in V. cholerae (122). An analysis of HutZ in vitro indicated that it has a high affinity for heme and degrades it via the same intermediates as heme oxygenase (123). Thus, HutZ may serve to release iron from heme following transport.…”
Section: Transport Of Iron Complexesmentioning
confidence: 99%
“…Furthermore, the biological degradation of heme (iron-protoporphyrin) plays a variety of critical functions in living organisms [39]; an enzyme termed heme oxygenase (HO) has already been reported to catalyze the regiospecific conversion of heme into biliverdin, carbon monoxide (CO), and a free ferrous iron via three successive oxygenation reactions [40] (Scheme 4). The literature contains numerous reports exemplifying other types of heme degradation enzymes, e.g., the HutZ protein in the heme utilization (Hut) system [41,42] and Mycobacterium tuberculosis enzyme MhuD [43]. Therefore, the results in the present work newly indicate that (1) oxygen will bind at the distal site for oxygen activation to be oxoferric (Fe III −O-O − ) species; (2) the iron of porphyrin/Fe and oxygen coordinates solely in water due to the promotion of oxoferryl (Fe IV =O) species; (3) ESR low-spin signals (g = 2.8, 2.22, and 1.72) disappear for oxygen activation with high-spin signal contamination; and (4) HasA can be used for cyclic deracemization in combination with NaBH4.…”
Section: * Reactionsmentioning
confidence: 99%